Work Stress, Workload, and Work Discipline on Work Satisfaction and Teacher Performance (Case Study in Akramunas Islamic Kindergarten, Pekanbaru) - Elfita; Sudarno; Nyoto; Fazal Mohamed Mohamed Sultan (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to determine and analyze the effect of work stress, workload, and work discipline on job satisfaction and teacher performance. The number of samples in this study was the entire study population of 45 teachers at the Pekanbaru Akramunas Foundation. Data collection techniques using a Likert scale. This study uses Smart PLS (Partial Least Squares) to prove that job stress has a negative effect on job satisfaction; workload has an insignificant positive effect on job satisfaction; Work discipline has a significant positive effect on job satisfaction; Work stress has no significant positive effect on teacher performance; Workload has no significant positive effect on work performance; Work Discipline has no significant negative effect on work performance and. Job satisfaction has a significant positive effect on teacher work performance.